Integrated formal methods : 12th International Conference, IFM 2016, Reykjavik, Iceland, June 1-5, 2016, Proceedings /: 12th International Conference, IFM 2016, Reykjavik, Iceland, June 1-5, 2016, Proceedings. (2016) - Unknown
No abstract available